2017
DOI: 10.1093/toxsci/kfx030
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Highlight: Periodic Exposure to Smartphone-Mimic Low-Luminance Blue Light Induces Retina Damage Through Bcl-2/BAX-Dependent Apoptosis

Abstract: Blue light-induced phototoxicity plays an important role in retinal degeneration and might cause damage as a consequence of smartphone dependency. Here, we investigated the effects of periodic exposure to blue light-emitting diode in a cell model and a rat retinal damage model. Retinal pigment epithelium (RPE) cells were subjected to blue light in vitro and the effects of blue light on activation of key apoptotic pathways were examined by measuring the levels of Bcl-2, Bax, Fas ligand (FasL), Fas-associated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 34 publications
5
30
0
Order By: Relevance
“…3A). Moreover, BLL downregulated the protein expression of procaspase-3 and procaspase-8, resulting in more cleavage forms of caspase-3 and caspase-8 after BLL exposure, which is consistent with our previous study [19]. To evaluate the protective effects of CTE further, different concentrations of CTE were applied to BLL-exposed RPE cells (Fig.…”
Section: Cte Inhibits Bll-induced Apoptosis In Rpe Cells By Regulatinsupporting
confidence: 89%
See 3 more Smart Citations
“…3A). Moreover, BLL downregulated the protein expression of procaspase-3 and procaspase-8, resulting in more cleavage forms of caspase-3 and caspase-8 after BLL exposure, which is consistent with our previous study [19]. To evaluate the protective effects of CTE further, different concentrations of CTE were applied to BLL-exposed RPE cells (Fig.…”
Section: Cte Inhibits Bll-induced Apoptosis In Rpe Cells By Regulatinsupporting
confidence: 89%
“…Previously, we found that low-intensity long-term BLL exposure induces retinopathy in a rat model [19]; as a continuation of that study, we orally administered CTE to BN rats. BL-induced retinal degeneration and damage has been studied in other models [37,38].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 86%
See 2 more Smart Citations
“…In real life, one source of blue light is digital screens. Studies have suggested that periodic exposure to smartphone‐like low‐luminance blue light induces photoreceptor atrophy, decreases retinal thickness, and injures neuron transduction in the retina . Additionally, the RPE cells of STGD1 patients with higher oxygen uptake and light absorption by lipofuscin granules are more susceptible to photo‐oxidative stress than age‐matched controls …”
Section: Introductionmentioning
confidence: 99%